ROLE AND FUNCTIONS OF ACADEMIC AND TEACHING STAFF IN ACCOMPLISHING THE TASKS OF ENVIRONMENTAL EDUCATION - Demeshkant, Natalia A. (Educological discourse, 2015)
This article analyzes the professional and environmental competence of academic and teaching staff. Considerable attention is paid to the definition of the agricultural universities staff’s functions on the formation of ecological consciousness of future specialists of the agrarian sector. A comparison of the teacher’s functions in accordance with traditional and modern educational models has done. Highlighted in the formation of the staff’s willingness to achieve the goals of environmental education; identify and characterize its levels.